2009
DOI: 10.1590/s1516-35982009000500023
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intraruminal infusion of propionic acid and forage to concentrate levels on intake, digestibility and rumen characteristics in young bulls

Abstract: -This study aimed to evaluate the effect of intraruminal infusion of propionic acid (RPA) associated to two (80:20 and 60:40) forage:concentrate ratios (FCR), for young bulls. Four Holstein × Zebu crossbred young bulls with average age of 7 months and 160 kg of body weight (BW) were distributed to a 4 × 4 Latin square design. A total mixed ration, isonitrogenous diets, was ad libitum fed to animals. The propionic acid was obtained by fermentation of reconstituted milk whey by the consortium of bacteria Entero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…The lower tendency of the pH with supplementation of E. faecium SROD could be related to the production of organic acids by the bacterium. Indeed, a previous study on E. faecium demonstrated that it increased the levels of organic acids such as acetate, propionate, and succinate (Ribeiro et al 2009).…”
Section: Discussionmentioning
confidence: 95%
“…The lower tendency of the pH with supplementation of E. faecium SROD could be related to the production of organic acids by the bacterium. Indeed, a previous study on E. faecium demonstrated that it increased the levels of organic acids such as acetate, propionate, and succinate (Ribeiro et al 2009).…”
Section: Discussionmentioning
confidence: 95%
“…During the dry-off period, cows are typically transitioned to a diet primarily composed of forage with a lower percentage of grain ( Dancy et al, 2019 ), which could impact the metabolic response. For example, propionic acid is a volatile fatty acid produced during rumen fermentation of carbohydrates, and its higher levels may reflect increased fermentation of forage-based diets, particularly grasslage ( Ribeiro et al, 2009 ). Compounds like citrulline, guanidinacetic acid, oxobutanoic acid, riboflavin, myristoyl ethanolamide, and coenzyme Q10 are involved in energy metabolism, amino acid metabolism, and cellular processes, and their levels may be influenced by metabolic shifts.…”
Section: Discussionmentioning
confidence: 99%
“…Lactose is a substrate from the genus Enterococcus sp that produces lactate. This is used as an energy source by bacteria of the genus Veilonella sp, which has propionic acid among its end products of the fermentation (Ribeiro et al, 2009). …”
Section: Introductionmentioning
confidence: 99%